-4(-8k+5)+7=243

Simple and best practice solution for -4(-8k+5)+7=243 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-8k+5)+7=243 equation:



-4(-8k+5)+7=243
We move all terms to the left:
-4(-8k+5)+7-(243)=0
We add all the numbers together, and all the variables
-4(-8k+5)-236=0
We multiply parentheses
32k-20-236=0
We add all the numbers together, and all the variables
32k-256=0
We move all terms containing k to the left, all other terms to the right
32k=256
k=256/32
k=8

See similar equations:

| 1=1-8p+8p | | 1/4m^2+m=0 | | 8b+3+5=16 | | 11x+3+4x+12=180 | | -14=a+6a | | 12+4b=2b-20 | | 3x-8=55-6x | | 109x+1=1/2(127x+93) | | 36=y+17 | | 2+1.5y=7 | | 9=b+3+3 | | 3(x+10)-3=72-2x | | x(2x-250)=2858 | | -50x^2-40x-8=0 | | 0=-16x^2-112x+125 | | 48x^2+26x=35 | | X^+4x+4=10 | | x-6=1-(-6) | | 0=b-5+4b | | 4x+2(x-1)=3x+9 | | 27x-32x=10-15 | | 25-5/2x=5 | | 12.5=1.25-y | | 17x+5=-4(4x+5) | | (x-6)(2x-14)=(3)(8) | | 8-8=16x+11x | | 3x-11=8x=21 | | 3x^2+5x+2=3x^2+5x+2 | | -3z=8+2z-12 | | 3x−5=19; | | 4/5=y-7/10 | | 15÷3+x÷6=30 |

Equations solver categories